Updates and advances on pharmacological properties of Taraxacum mongolicum Hand.-Mazz and its potential applications. (30th March 2022) - Zhang, Yan; Hu, Ying-Fan; Li, Wei; Xu, Guang-Ya; Wang, Kun-Rong; Li, Lin; Luo, Hao; Zou, Liang; Wu, Jia-Si
Highlights: TMHM has a variety of pharmacological activities. There are seven categories of main bioactive components in TMHM. TMHM has been widely applied in food, nutraceutical, and cosmetic industry. Pharmacokinetics and toxicology of TMHM have also been discussed. Abstract: As a well-recognized dietary and medicinal plant, Taraxacum mongolicum Hand.-Mazz (TMHM) has been used for making wines, candies, energy drinks, and other functional foods. The TMHM contains a diverse range of active phytoconstituents, including flavonoids, triterpenoids, phenolic acids, sesquiterpene lactones, pigments, coumarins and sterols. Recent pharmacological evidence has revealed multiple biological effects of TMHM, including anti-inflammatory, antioxidant, antibacterial, and gastric-protective effects, which contribute to the ameliorative effects of TMHM on inflammation-associated diseases, constipation, gastric disorders, empyrosis, hyperlipidemia, and swollen carbuncles. Although recent advances have highlighted the potential of TMHM to be applied in the clinical practice, food, and nutraceutical industry, the mechanistic understanding and systematic information on TMHM are still scarce. Here, in this timeline review, we have attempted to compile literary documents on pharmacological potential of TMHM concerning its chemical composition, biological activities, toxicity, and pharmacokinetics to promote further researches on clinical and therapeutic potential of TMHM and its food/nutraceutical applications.